2022
DOI: 10.1021/acsanm.1c04473
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Monitoring of Scale Effects on Phase Selection and Plasmonic Shifts during the Growth of AgCu Alloy Nanostructures for Anticounterfeiting Applications

Abstract: Tailoring of plasmon resonances is essential for applications in anticounterfeiting. This is readily achieved by tuning the composition of alloyed metal clusters; in the simplest case, binary alloys are used. Yet, one challenge is the correlation of cluster morphology and composition with the changing optoelectronic properties. Hitherto, the early stages of metal alloy nanocluster formation in immiscible binary systems such as silver and copper have been accessible by molecular dynamics (MD) simulations and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 73 publications
(144 reference statements)
1
6
0
Order By: Relevance
“…Further, a significant target history effect was also clearly discernible, due to the redepositions. The temporal evolution of the phase separation of immiscible Ag–Cu nanoalloys was followed by another very recent study employing a combination of ex situ (Transmission Electron Microscopy, TEM) and in situ (optical spectroscopy, Grazing-Incidence Small- and Wide-angle X-ray Scattering, GISAXS/GIWAXS) methods, 101 and deducing the effective diffusion coefficients of the two elements (confirming previous simulation results on the same 102 and different systems 103 ). The nanoparticles reported within this study are promising for potential anti-counterfeiting applications.…”
Section: Instrumentation Development Responsessupporting
confidence: 70%
“…Further, a significant target history effect was also clearly discernible, due to the redepositions. The temporal evolution of the phase separation of immiscible Ag–Cu nanoalloys was followed by another very recent study employing a combination of ex situ (Transmission Electron Microscopy, TEM) and in situ (optical spectroscopy, Grazing-Incidence Small- and Wide-angle X-ray Scattering, GISAXS/GIWAXS) methods, 101 and deducing the effective diffusion coefficients of the two elements (confirming previous simulation results on the same 102 and different systems 103 ). The nanoparticles reported within this study are promising for potential anti-counterfeiting applications.…”
Section: Instrumentation Development Responsessupporting
confidence: 70%
“…However, this is not a comprehensive list of the many studies which, to date, involved plasmonic nanoalloys, sometimes also including photodetection, photovoltaics, chemical transformations, linear spectroscopy and circular dichroism. The possibility of tailoring the LSP, offered by alloying, is crucial also for applications in anticounterfeiting and electrochromic color switching [197] …”
Section: Applicationsmentioning
confidence: 99%
“…The possibility of tailoring the LSP, offered by alloying, is crucial also for applications in anticounterfeiting and electrochromic color switching. [197] …”
Section: Applicationsmentioning
confidence: 99%
“…Bimetallic nanocrystals have attracted great interest as they offer an extra degree of freedom to fine-tune their structures, phases, and properties in comparison with the elemental ones. Diverse configurations and synergistic effects can be obtained in these nanocrystals, which frequently enable novel functionalities facilitating diverse applications in such as optics, [1][2][3][4][5][6] plasmonics, [7][8][9][10][11][12] catalysis, [13][14][15][16][17][18][19][20] sensor, [21][22][23][24][25][26][27][28] and biomedicine. [29][30][31][32][33] For example, Xu et al have reported that bimetallic AuAg core-shell catalysts show much higher catalytic activity than elemental Au and Ag catalysts in reducing 4-nitrophenol.…”
Section: Introductionmentioning
confidence: 99%